Znaczenie przejścia na euro z punktu widzenia polityki pieniężnej realizowanej w Polsce - Sieńko-Kowalska, Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
In May 2004, Poland became a full member of the European Community, but not a member with full membership rights. The introduction of the European Union means for Poland to accept a common monetary policy together with the other euro zone countries. First of all our country must perform the Maastricht convergence criteria. They are characterised by the stability of prices, the level of long-term interest rates and exchange rate stability. The introduction of the euro in Poland will result in the elimination of transaction costs connected with existence of the exchange rate between the zloty and the euro. Adopting the single currency will support the integration of the Polish financial market into that of the euro zone. It also should improve the conditions of financing for Polish enterprises. As a result of introducing the euro in Poland, will be cost of losing independent monetary policy. But the same way benefits should be large because the accession to the euro zone is an investment in long term economic growth.
Keywords: Euro; polityka pieniężna; Polska